“Feelings and Fitness” Not “Feelings or Fitness”–The Raison d'être of Conservation Welfare, Which Aligns Conservation and Animal Welfare Objectives - Beausoleil, Ngaio J.; Mellor, David J.; Baker, Liv; Baker, Sandra E.; Bellio, Mariagrazia; Clarke, Alison S.; Dale, Arnja; Garlick, Steve; Jones, Bidda; Harvey, Andrea; Pitcher, Benjamin J.; Sherwen, Sally; et al. (Frontiers in Veterinary Science, 2018)
Increasingly, human activities, including those aimed at conserving species and ecosystems (conservation activities) influence not only the survival and fitness but also the welfare of wild animals. Animal welfare relates to how an animal is experiencing its life and encompasses both its physical and mental states. While conservation biology and animal welfare science are both multi-disciplinary fields that use scientific methods to address concerns about animals, their focus and objectives sometimes appear to conflict. However, activities impacting detrimentally on the welfare of individual animals also hamper achievement of some conservation goals, and societal acceptance is imperative to the continuation of conservation activities. Thus, the best outcomes for both disciplines will be achieved through collaboration and knowledge-sharing. Despite this recognition, cross-disciplinary information-sharing and collaborative research and practice in conservation are still rare, with the exception of the zoo context. This paper summarizes key points developed by a group of conservation and animal welfare scientists discussing scientific assessment of wild animal welfare and barriers to progress. The dominant theme emerging was the need for a common language to facilitate cross-disciplinary progress in understanding and safeguarding the welfare of animals of wild species. Current conceptions of welfare implicit in conservation science, based mainly on ‘fitness’ (physical states), need to be aligned with contemporary animal welfare science concepts which emphasize the dynamic integration of ‘fitness’ and ‘feelings’ (mental experiences) to holistically understand animals’ welfare states. The way in which animal welfare is characterized influences the way it is evaluated and the emphasis put on different features of welfare as well as the importance placed on the outcomes of such evaluations and how that information is used, for example in policy development and decision-making. Salient examples from the New Zealand and Australian context are presented to illustrate. To genuinely progress our understanding and evaluation of wild animal welfare and optimize the aims of both scientific disciplines, conservation and animal welfare scientists should work together to evolve and apply a common understanding of welfare. To facilitate this, we propose the formal development of a new discipline, Conservation Welfare, integrating the expertise of scientists from both fields.